Water–swellable Rubber Based on Hydroxyethylcellulose Grafted Polyacrylamide and Epoxidized Natural Rubber Blends - Ajaman Adair (Prince of Songkla University, 2023)
Thesis (Ph.D., Polymer Technology)--Prince of Songkla University, 2022